2022
DOI: 10.1021/acs.chemrestox.2c00159
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Aldehyde Flavorant-Acetal Formation in E-Liquids with Different E-Cigarette Solvents and Common Additives Studied by 1H NMR Spectroscopy

Abstract: Flavorants, nicotine, and organic acids are common additives found in the e-liquid carrier solvent, propylene glycol (PG) and/or glycerol (GL), at various concentrations. Some of the most concentrated and prevalent flavorants in e-liquids include trans-cinnamaldehyde, vanillin, and benzaldehyde. Aldehyde flavorants have been shown to react with PG and GL to form flavorant-PG and -GL acetals that have unique toxicity properties in e-liquids before aerosolization. However, there is still much that remains unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…157 Interestingly, acetalization has been reported to occur at a faster rate and to produce higher yields when vapers utilize e-liquids with higher ratios of VG relative to PG. 158 These data reinforce the issue that reaction products formed between flavor aldehydes and excipient chemicals likely have differential toxicological properties as compared to their parent compounds and may thus contribute to the health effects of vaped aerosols within the lungs of e-cigarette users. 113,157,159,160 A study by Tierney and colleagues that identified and quantified the flavoring constituents in 30 popular e-cigarette products reported menthol concentrations ranging from 5.7 to 21.6 mg/mL (0.57 to 2.16% w/v), which are comparable to concentrations reported for the menthol content of traditional menthol cigarettes, that is, 3 to 20 mg per cigarette.…”
Section: Identified Chemical Biomarkers/chemical Compositions Within ...supporting
confidence: 57%
See 1 more Smart Citation
“…157 Interestingly, acetalization has been reported to occur at a faster rate and to produce higher yields when vapers utilize e-liquids with higher ratios of VG relative to PG. 158 These data reinforce the issue that reaction products formed between flavor aldehydes and excipient chemicals likely have differential toxicological properties as compared to their parent compounds and may thus contribute to the health effects of vaped aerosols within the lungs of e-cigarette users. 113,157,159,160 A study by Tierney and colleagues that identified and quantified the flavoring constituents in 30 popular e-cigarette products reported menthol concentrations ranging from 5.7 to 21.6 mg/mL (0.57 to 2.16% w/v), which are comparable to concentrations reported for the menthol content of traditional menthol cigarettes, that is, 3 to 20 mg per cigarette.…”
Section: Identified Chemical Biomarkers/chemical Compositions Within ...supporting
confidence: 57%
“…Indeed, menthol’s effectiveness in reducing both the perceived airway irritation and overall harshness that is typically produced during the inhalation of e-liquids containing high nicotine concentrations is thought to contribute to the sensory impact of the e-liquid when vaped and may increase nicotine intake. , The chemical itself is known to evoke oxidative and inflammatory responses and may lead to issues with the maintenance of epithelial barrier function within the lung. , Common e-cigarette flavorants such as menthol and various aldehydes (e.g., vanillin) are also known to react with alcohols (such as PG and VG) to form acetals . Interestingly, acetalization has been reported to occur at a faster rate and to produce higher yields when vapers utilize e-liquids with higher ratios of VG relative to PG . These data reinforce the issue that reaction products formed between flavor aldehydes and excipient chemicals likely have differential toxicological properties as compared to their parent compounds and may thus contribute to the health effects of vaped aerosols within the lungs of e-cigarette users. ,,, …”
Section: Identified Chemical Biomarkers/chemical Compositions Within ...mentioning
confidence: 99%
“…Furfural PG and VG acetals, valeraldehyde PG and VG acetals, veretraldehyde PG and VG acetals, p-anisaldehyde PG and VG acetals, and piperonal VG acetal were confirmed for the first time, expanding on the acetals identified in previous studies. 7,8,16,17,25 Adducts were shown to form under general eliquid storage conditions (room temperature, partial light) when aldehydes were exposed to PG and VG. No flavoring molecules other than aldehydes and ketones within this project were identified to react with PG or VG.…”
Section: Determination Of Reactivity Of Flavoring Moleculesmentioning
confidence: 99%
“…Recently, a paper published by Kerber and Peyton examined the PG acetal formation rates and yields in the presence of water, nicotine, benzoic acid, and vegetable glycerine using 1 H NMR spectroscopy. 25 It was found that acetals form more rapidly and at higher yields when aldehydes are in the presence of higher VG ratios (relative to PG), little water, no nicotine, nicotine with excess organic acids, or organic acids without nicotine. This kinetics study strengthens the results presented here, as it confirms that the rates of reaction for aldehyde acetal formation is varied and dependent on the parent flavor molecule.…”
Section: Determination Of Reactivity Of Flavoring Moleculesmentioning
confidence: 99%
“…We have established a variety of methods for determining the flavorant and toxicological profiles of e-liquids before and after aerosolization using GC–MS and NMR spectroscopy. GC–MS has higher sensitivity in analyzing volatile compounds compared to NMR and is typically used to determine the flavorant profile. However, NMR can identify and quantify some species not detectable by GC–MS.…”
mentioning
confidence: 99%